2008
DOI: 10.1097/qai.0b013e31817bebb3
|View full text |Cite
|
Sign up to set email alerts
|

Poor Initial CD4+ Recovery With Antiretroviral Therapy Prolongs Immune Depletion and Increases Risk for AIDS and Non-AIDS Diseases

Abstract: Background Low CD4+ increases risk for both AIDS- and non–AIDS-related morbidity and mortality. The magnitude of CD4+ recovery early after initial antiretroviral therapy (ART) is important in the ultimate duration of immune depletion. Methods We examined CD4+ recovery among 850 participants in the Community Program for Clinical Research on AIDS Flexible Initial Retrovirus Suppressive Therapies study with virologic suppression (ie, achieved an HIV RNA level <400 copies/mL) with 8 months of initial ART and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 32 publications
6
107
4
2
Order By: Relevance
“…The fact that cells carrying infectious proviruses can expand by cell division complicates the problem of eliminating all of the HIV-1 proviruses that make up the HIV-1 reservoir. The patient we describe had advanced HIV infection at presentation and, although clinically stable for a number of years without opportunistic infections, he never achieved robust CD4 recovery while undergoing cART; it is possible that overall, immune surveillance was weak in this patient because of the poor recovery of his T cells during cART (12,13), which may have impaired tumor surveillance. It is likely that only a fraction of the cells in the clone were producing virus at any given time, which could help the clone escape from HIV-1-specific immune surveillance.…”
Section: Discussionmentioning
confidence: 96%
“…The fact that cells carrying infectious proviruses can expand by cell division complicates the problem of eliminating all of the HIV-1 proviruses that make up the HIV-1 reservoir. The patient we describe had advanced HIV infection at presentation and, although clinically stable for a number of years without opportunistic infections, he never achieved robust CD4 recovery while undergoing cART; it is possible that overall, immune surveillance was weak in this patient because of the poor recovery of his T cells during cART (12,13), which may have impaired tumor surveillance. It is likely that only a fraction of the cells in the clone were producing virus at any given time, which could help the clone escape from HIV-1-specific immune surveillance.…”
Section: Discussionmentioning
confidence: 96%
“…Although HAART accounts for the significant decrease in AIDSrelated morbidity and mortality seen in recent years [21], an increased rate of AIDS-related complications such as neurocognitive disorders, nephropathy and malignancies are being observed in patients with poor initial CD4 + recovery and in patients with a CD4 + count higher than 200 cells per mm 3 [22,23]. This could be caused by prolonged viral persistence, chronic immune activation, incomplete immune reconstitution and/or accelerated immune senescence.…”
Section: Hiv and Its Treatment: Advantages And Some Limits Of Haartmentioning
confidence: 99%
“…[78][79][80][81][82][83] Some suggests that these finding may be linked with higher adherence in older patients, 78,[84][85] but other authors reported a higher risk of inadequate adherence in HIV patients who have other comorbidities and take other medications besides HAART. [86][87] While virological response seems not to be influenced by age, at least biologically, older patients have lower CD4C T-cell gain compared with younger persons, [88][89][90][91][92][93][94][95] even when adjusted for antiretroviral therapy regimens. This is particularly relevant considering that lower CD4 T-cell counts are not only linked to HIV-related opportunistic infections and malignancies, but also lead to higher risk of non-AIDS-related comorbidities, adding to the already elevated risk conferred by age.…”
Section: Clinical Outcomementioning
confidence: 99%